The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1371/journal.pone.0295816
|View full text |Cite
|
Sign up to set email alerts
|

Molecular effects of polystyrene nanoplastics on human neural stem cells

Raquel Martin-Folgar,
Mª Carmen González-Caballero,
Mónica Torres-Ruiz
et al.

Abstract: Nanoplastics (NPs) have been found in many ecological environments (aquatic, terrestrial, air). Currently, there is great concern about the exposition and impact on animal health, including humans, because of the effects of ingestion and accumulation of these nanomaterials (NMs) in aquatic organisms and their incorporation into the food chain. NPs´ mechanisms of action on humans are currently unknown. In this study, we evaluated the altered molecular mechanisms on human neural stem cell line (hNS1) after 4 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…The researchers found that nanoplastics affected gene expression in a concentration-dependent manner, with some genes being upregulated and others downregulated. They particularly observed significant changes in the expression of stress response genes, including hsp27/hspB1, hsp70/hspA5, and hsp90α, after exposure to nanoplastics 29 .…”
Section: Methodsmentioning
confidence: 99%
“…The researchers found that nanoplastics affected gene expression in a concentration-dependent manner, with some genes being upregulated and others downregulated. They particularly observed significant changes in the expression of stress response genes, including hsp27/hspB1, hsp70/hspA5, and hsp90α, after exposure to nanoplastics 29 .…”
Section: Methodsmentioning
confidence: 99%